Dedi Mulyadi's Leadership Style as Governor of West Java: Between Sundanese Culture and Islamic Law - Sri Yuliana Evnawati (Research Synergy Foundation, 2025)
This study examines how Dedi Mulyadi’s leadership integrates Sundanese cultural values with Islamic Sharia principles, illustrating the dynamics of local Islamic leadership in West Java. It aims to contribute to the discourse on contextual Islamic leadership models rooted in local traditions. As a public figure known for his culturally grounded approach to governance, Dedi Mulyadi exemplifies an authentic leadership style that synthesizes traditional Sundanese values, such as gotong royong (cooperation), silih asah, silih asih, and environmental harmony, with Islamic virtues like justice, amanah (trustworthiness), and shura (consultation). This research adopts a descriptive qualitative approach, employing literature review, media analysis, and discourse analysis of public speeches and policies to explore his leadership model. The findings reveal that Mulyadi’s leadership is inclusive, humanistic, and transformative, offering a model of integrated cultural religious governance that resonates strongly within the local community. Understanding this synthesis is crucial amid contemporary governance challenges marked by increasing identity-based political tensions, cultural fragmentation, and the need for value-driven leadership at the local level. By highlighting a model that bridges tradition and religion, this study underscores the potential of culturally embedded Islamic leadership in promoting social harmony, ethical governance, and regional policy innovation. The study recommends further development of such frameworks as viable alternatives for identity-conscious, socially sustainable local governance.